Raman spectroscopy a promising technique for investigations of metallothioneins. - Torreggiani, Armida; Tinti, Anna (Metallomics : integrated biometal science, 2010)
Metallobiomolecules are highly elaborated coordination complexes, and their fundamental metal-ligand interactions are critical components of metalloprotein folding, assembly, stability, electrochemistry, and catalytic function. Herein, we have described the benefits in using Raman spectroscopy to define the metal-ion binding properties of MTs toward metal ions such as Zn(ii) and Cd(ii). In particular, this vibrational technique can shed light on the secondary structures eventually present in MTs and the ligands involved in metal coordination. The oxidation state of Cys residues and their participation in the metal chelation can be clearly defined, as well as the eventual involvement of His residues. With regards to exogenous metal ligands such as sulfide anions, their presence can be identified by some marker bands whose intensity is linearly correlated with sulfide/metal molar ratio. Finally, Raman can be also an useful tool for providing information on the favourite sites of the radical attack and radical-induced modification in protein folding. In conclusion, many advantages such as the capability of defining local regions in large complexes and detecting several structural features at the same time, the ability in supporting mechanisms, as well as the requirement of low sample amount, make to propose Raman spectroscopy, in coupling with analytical techniques such as atomic emission spectroscopy, gas chromatography, and circular dichroism, as one of the most promising experimental strategies in the research on structure-activity relationships in MTs.
Keywords: copper; Copper: chemistry; Copper: metabolism; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Spectrum Analysis, Raman; Spectrum Analysis, Raman: methods; Structure-Activity Relationship; Zinc; Zinc: chemistry; Zinc: metabolism

The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. - Domenech, Jordi; Orihuela, Ruben; Mir, Gisela; Molinas, Marisa; Atrian, Silvia; Capdevila, Merce (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.
The following values have no corresponding Zotero field: accession-num: 17503092
Keywords: cadmium; Cadmium: chemistry; Cadmium–His binding; Drug; Glutathione; Metabolic Detoxication; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Phytochelatins; Plant metallothionein; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Protein Binding; Protein Conformation; Quercus; Recombinant Proteins; Sulfide ligands; yeast complementation

The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. - Domenech, Jordi; Orihuela, Ruben; Mir, Gisela; Molinas, Marisa; Atrian, Silvia; Capdevila, Merce (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.
Keywords: cadmium; Cadmium: chemistry; Cadmium–His binding; Drug; Glutathione; Metabolic Detoxication; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Phytochelatins; Plant metallothionein; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Protein Binding; Protein Conformation; Quercus; Recombinant Proteins; Sulfide ligands; yeast complementation

Structural study of the zinc and cadmium complexes of a type 2 plant (Quercus suber) metallothionein: Insights by vibrational spectroscopy - Domènech, J; Tinti, Anna; Capdevila, M (Biopolymers, 2007)
Zn- and Cd-complexes of Quercus suber metallothionein (QsMT) were obtained by in vivo-synthesis, in order to obtain physiologically representative aggregates, and characterized by spectrometric and spectroscopic methods. The secondary structure elements and the coordination environments of the metal binding sites of the two aggregates were determined, as well as the main metal-containing species formed. The results obtained from the analysis of the Raman and IR spectra reveal that these metal-MT complexes predominantly contain b-sheet elements (about 60%), whereas they lack ahelices. These structural features slightly depend on the divalent metal bound. In particular, Cd II binding to QsMT induces a slight increase of the b-sheet percentage, as well as a decrease in b-turn elements with respect to Zn II binding. Conversely, the in vivo capability of QsMT to inglobe metal and sulﬁde ions is metal-depending. Spectroscopic vibrational data also conﬁrm the presence of sulﬁde ligands in the metal clusters of both Zn- and Cd-QsMT, while the participation of the spacer His residue in metal coordination was only found in Cd-QsMT, in agreement with the CD results. Overall data suggest different coordination environments for Zn II and Cd II ions in QsMT
Keywords: IR spectroscopy; metal complexes; metallothionein; Raman spectroscopy; sulfur ligand

Structural study of the zinc and cadmium complexes of a type 2 plant (Quercus suber) metallothionein: Insights by vibrational spectroscopy - Domènech, J.; Tinti, Anna; Capdevila, M. (Biopolymers, 2007)
Zn- and Cd-complexes of Quercus suber metallothionein (QsMT) were obtained by in vivo-synthesis, in order to obtain physiologically representative aggregates, and characterized by spectrometric and spectroscopic methods. The secondary structure elements and the coordination environments of the metal binding sites of the two aggregates were determined, as well as the main metal-containing species formed. The results obtained from the analysis of the Raman and IR spectra reveal that these metal-MT complexes predominantly contain b-sheet elements (about 60%), whereas they lack ahelices. These structural features slightly depend on the divalent metal bound. In particular, Cd II binding to QsMT induces a slight increase of the b-sheet percentage, as well as a decrease in b-turn elements with respect to Zn II binding. Conversely, the in vivo capability of QsMT to inglobe metal and sulﬁde ions is metal-depending. Spectroscopic vibrational data also conﬁrm the presence of sulﬁde ligands in the metal clusters of both Zn- and Cd-QsMT, while the participation of the spacer His residue in metal coordination was only found in Cd-QsMT, in agreement with the CD results. Overall data suggest different coordination environments for Zn II and Cd II ions in QsMT
Keywords: IR spectroscopy; metal complexes; metallothionein; Raman spectroscopy; sulfur ligand

Plant metallothionein domains: functional insight into physiological metal binding and protein folding - Domenech, Jordi; Mir, Gisela; Huguet, Gemma; Capdevila, Merce; Molinas, Marisa; Atrian, Silvia (BIOCHIMIE, 2006)
Plant metallothioneins (MTs) differ from animal MTs by a peculiar sequence organization consisting of two short cysteine-rich terminal domains linked by a long cysteine-devoid spacer. The role of the plant NIT domains in the protein structure and functionality is largely unknown. Here, we investigate the separate domain contribution to the in vivo binding of Zn and Cu and to confer metal tolerance to CUP1-null yeast cells of a plant type 2 NIT (QsMT). For this purpose, we obtained three recombinant peptides that, respectively, correspond to the single N-terminal (N25) and C-terminal (C18) cysteine-rich domains of QsMT, and a chimera in which the spacer is replaced with a four-glycine bridge (N25-C18). The metal-peptide preparations recovered from Zn- or Cu-enriched cultures were characterized by ESI-MS, ICP-OES and CD and UV-vis spectroscopy and data compared to full length QsMT. Results are consistent with QsMT giving rise to homometallic Zn- or Cu-MT complexes according to a hairpin model in which the two Cys-rich domains interact to form a cluster. In this model the spacer region does not contribute to the metal coordination. However, our data from Zn-QsMT (but not from Cu-QsMT) support a fold of the spacer involving some interaction with the metal core. On the other hand, results from functional complementation assays in endogenous MT-defective yeast cells suggest that the spacer region may play a role in Cu-QsMT stability or subcellular localization. As a whole, our results provide the first insight into the structure/function relationship of plant MTs using the analysis of the separate domain abilities to bind physiological metals. (c) 2005 Elsevier SAS. All rights reserved.
Keywords: Cu-aggregates; metallothionein; MT dimers; Quercus suber; separate Cys-rich domains; spacer region; yeast complementation; Zn-aggregates

Plant metallothionein domains: functional insight into physiological metal binding and protein folding - Domenech, Jordi; Mir, Gisela; Huguet, Gemma; Capdevila, Merce; Molinas, Marisa; Atrian, Silvia (BIOCHIMIE, 2006)
Plant metallothioneins (MTs) differ from animal MTs by a peculiar sequence organization consisting of two short cysteine-rich terminal domains linked by a long cysteine-devoid spacer. The role of the plant NIT domains in the protein structure and functionality is largely unknown. Here, we investigate the separate domain contribution to the in vivo binding of Zn and Cu and to confer metal tolerance to CUP1-null yeast cells of a plant type 2 NIT (QsMT). For this purpose, we obtained three recombinant peptides that, respectively, correspond to the single N-terminal (N25) and C-terminal (C18) cysteine-rich domains of QsMT, and a chimera in which the spacer is replaced with a four-glycine bridge (N25-C18). The metal-peptide preparations recovered from Zn- or Cu-enriched cultures were characterized by ESI-MS, ICP-OES and CD and UV-vis spectroscopy and data compared to full length QsMT. Results are consistent with QsMT giving rise to homometallic Zn- or Cu-MT complexes according to a hairpin model in which the two Cys-rich domains interact to form a cluster. In this model the spacer region does not contribute to the metal coordination. However, our data from Zn-QsMT (but not from Cu-QsMT) support a fold of the spacer involving some interaction with the metal core. On the other hand, results from functional complementation assays in endogenous MT-defective yeast cells suggest that the spacer region may play a role in Cu-QsMT stability or subcellular localization. As a whole, our results provide the first insight into the structure/function relationship of plant MTs using the analysis of the separate domain abilities to bind physiological metals. (c) 2005 Elsevier SAS. All rights reserved.
The following values have no corresponding Zotero field: pub-location: 23 RUE LINOIS, 75724 PARIS, FRANCE publisher: ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER
Keywords: Cu-aggregates; metallothionein; MT dimers; Quercus suber; separate Cys-rich domains; spacer region; yeast complementation; Zn-aggregates